Anti-diabetic effect of betulinic acid on streptozotocin-nicotinamide induced diabetic male mouse model - Golshan Arzani Birgani; Akram Ahangarpour; Layasadat Khorsandi; Hadi Fathi Moghaddam (Universidade de São Paulo, 2018)
ABSTRACT Diabetes is a metabolic disease caused by abnormal insulin secretion or action. In the present study, the effects of betulinic acid (BA, a triterpene) are evaluated on glucose, α-amylase and plasma insulin levels, insulin resistance and the histopathology of pancreatic islets in streptozotocin-nicotinamide (STZ-NA) diabetic mice. Seventy adult male NMRI mice were randomly divided into seven groups: control, sham, diabetic, diabetic treated with BA (10, 20 and 40 mg/kg) and diabetic treated with metformin (200 mg/kg). Diabetes was induced in mice by intraperitoneal injection of streptozotocin 50 mg/kg after a dose of nicotinamide 120 mg/kg. Two weeks after treatment with BA, blood samples were collected for measuring glucose, α-amylase and insulin levels, and the pancreas was isolated for histopathology evaluation. Diabetes reduced the number and diameter of pancreatic islets, and increased α-amylase and insulin resistance. BA treatment reduced blood glucose, α-amylase and improved insulin sensitivity as well as pancreas histopathology. In addition, BA showed stronger effects on the pancreatic histology and insulin resistance compared to the metformin group.